Transformation of nad7 into the nuclear genome rescues the slow growth3 mutant in Arabidopsis. Issue 11 (2nd November 2018) - Hsieh, Wei-Yu; Lin, Sang-Chu; Hsieh, Ming-Hsiun
ABSTRACT: Plant pentatricopeptide repeat (PPR) proteins are mostly involved in chloroplast or mitochondrial RNA metabolism. However, direct evidence that correction of the molecular defects in the organelles can restore the plant phenotypes has yet to be demonstrated in a ppr mutant. Arabidopsis slow growth3 ( slo3 ), a ppr mutant, is impaired in the splicing of mitochondrial nad7 intron 2. Here, we have used slo3 as an example to demonstrate that transformation of correctly spliced nad7 into the nuclear genome and targeting the Nad7 subunit into mitochondria can restore complex I activity and plant phenotypes in the mutant. These results provide direct evidence that the strong growth and developmental phenotypes of the slo3 mutant are caused by defects in mitochondrial nad7 .